The effects of social support and relationship with the perpetrator on disclosure of sexual abuse : depression, anxiety and stress symptoms among sexually abused victims in Iceland - Helga Maren Hauksdóttir 1989- (2020)
Sexual violence can have severe consequences for those affected. It is important for victims to receive social support for their well-being and mental health. Relationships with perpetrators can affect the disclosure of sexual abuse. The current study examined gender differences on the effects of social support and relationship with perpetrators on disclosure of sexual abuse and symptoms of depression, anxiety, and stress. This study on trauma and mental health in the Icelandic population, was conducted by Reykjavik University and the participants were a random sample from the National Registry of Iceland that consisted of 747 respondents, participation involved answering questionnaires in a telephone survey. The results showed that females were more likely to be victims of sexual abuse, disclose sexual abuse, be victims of intrafamilial sexual abuse, and reported higher levels of depression, anxiety, and stress than males. No significant gender difference was found in the perception of social support and psychological symptoms, but higher support was associated with lower symptoms. Victims of intrafamilial abuse reported more symptoms of anxiety than extrafamilial victims. No relations were confirmed between the relationship with the perpetrator and perception of social support on disclosure of sexual abuse. When social support, relationship with the perpetrator, and disclosure were examined together in their relationship with depression, anxiety, and stress, social support was the only factor that was related to anxiety, depression, and stress symptoms among victims. Keywords: Psychology, sexual abuse, social support, disclosure, relationship with the perpetrator